2013
DOI: 10.1080/10408398.2011.596639
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Health Perspectives of Beans (Phaseolus vulgarisL.): An Overview

Abstract: Beans, the variants of Phaseolus vulagris, are nutritionally and economically important food crop in each part of the world. Besides providing nutrients such as multifaceted carbohydrates, elevated proteins, dietary fiber, minerals, and vitamins, these also contain rich variety of polyphenolic compounds with prospective health benefits. This review mainly focuses the important nutritional aspects of beans as well as their contribution in decreasing the risks of chronically degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
227
1
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(258 citation statements)
references
References 159 publications
7
227
1
23
Order By: Relevance
“…Similar results were obtained by Siger et al [32], who reported the highest level of these compounds in yellow lupine seeds (in particular in the Paris cv.). Furthermore, the authors emphasised that the antioxidant apigenin-6,8-di-Cpglucopyranoside and apigenin 7-O-β-Apium furanosyl-6,8-di-Cp-glucopyranoside discovered for the first time in [21,30,33,34]. The antioxidant properties of the legume seeds were determined by the ability to scavenge the DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Siger et al [32], who reported the highest level of these compounds in yellow lupine seeds (in particular in the Paris cv.). Furthermore, the authors emphasised that the antioxidant apigenin-6,8-di-Cpglucopyranoside and apigenin 7-O-β-Apium furanosyl-6,8-di-Cp-glucopyranoside discovered for the first time in [21,30,33,34]. The antioxidant properties of the legume seeds were determined by the ability to scavenge the DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…The high fibre content in legume seeds ensures their basificating properties, which balance the acidifying effects of meat, eggs, and cereal products. The combination of legume seeds with meat, eggs, or cheese increases the digestibility of proteins contained therein [21].…”
Section: Resultsmentioning
confidence: 99%
“…Os grãos de feijão apresentaram elevada quantidade de metabolitos totais. Resultados semelhantes aos encontrados por Boateng et al (2008); Hayat et al (2014); Luthria e Pastor-Corrales (2006); que reportaram valores de fenólicos totais (1917-5417 mg/100g), taninos (1910-4830 mg/100g), flavonoides (587-1414 mg/100g), antocianinas (213-470 mg/100g), proantocianidinas (51-313 mg/100g). Após o armazenamento foram verificadas reduções (p≤0,05) no conteúdo de metabolitos (fenóis totais, taninos totais, antocianinas totais, proantocianidinas torais e flavonoides totais) em todos os tratamentos, quando comparado ao início do armazenamento, porém as maiores reduções ocorreram nos grãos armazenados com 16% de umidade, associados a utilização da radiação (exceto para os taninos e antocianinas) como tratamento pré-armazenamento.…”
Section: Resultsunclassified
“…Common beans are rich in antioxidants which, among other components, provides flavonoids and phenolic acids ( Figure 2) [7]; likewise, this legume is a source for producing bioactive peptides (Table 2) obtained by enzymatic hydrolysis which confer antioxidant activity, antimutagenic effects [6] and an antihypertensive potential by inhibiting angiotensin converting enzyme [8,9]. In order to obtain maximum health benefits of whole grains, such as maize and beans, it is desirable to prepare mixtures from them; the additive and synergistic effects of biologically active components present in each whole grain may be responsible for the health benefits as the reduced risk of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Common bean (Phaseolus vulgaris L) plays an important role in the diet of Latin-American people, providing proteins, essential fatty acids, complex carbohydrates, vitamins and minerals [6]. Common beans are rich in antioxidants which, among other components, provides flavonoids and phenolic acids ( Figure 2) [7]; likewise, this legume is a source for producing bioactive peptides (Table 2) obtained by enzymatic hydrolysis which confer antioxidant activity, antimutagenic effects [6] and an antihypertensive potential by inhibiting angiotensin converting enzyme [8,9].…”
Section: Introductionmentioning
confidence: 99%